Facilitators and Barriers to the Implementation of iSPRINT: A Sport Injury Prevention Program in Junior High Schools. Issue 3 (May 2020) - Richmond, Sarah A.; Donaldson, Alex; Macpherson, Alison; Bridel, William; van den Berg, Carla; Finch, Caroline F.; Hagel, Brent; Emery, Carolyn A.
Abstract : Objectives: Sport injury is the leading cause of hospitalization in Canadian youth and represents a high burden to the health care system. This study aims to describe the facilitators and barriers to implementation of a sport injury prevention program in junior high school physical education (known as iSPRINT), previously shown to reduce the risk of sport-related injury in youth (age, 11-15 years). Methods: Focus group data were mapped onto constructs from the Consolidated Framework for Implementation Research (CFIR). Four schools that implemented iSPRINT participated in this study. Forty-seven key stakeholders (teachers, students, principals) participated in 9 semistructured focus groups and 4 interviews. The CFIR was used to guide the focus group discussions, data coding, and analysis using a qualitative content analysis approach. Results: Of the 22 applicable CFIR constructs, 16 were identified in the transcripts. The most significant facilitators to successful implementation efforts included evidence strength and quality, adaptability, implementation climate, culture, and having a high level of compatibility facilitated successful implementation efforts. Barriers to implementation included intervention complexity, planning, and readiness for implementation. Constructs that acted as both a facilitator and a barrier, depending on the context, were self-efficacy, execution, and individual identification with the organization. Conclusions: Participants in this study reported positive attitudes about implementing iSPRINT, citing evidence strength, adaptability, and constructs related to the organizational setting that contributed to successful implementation. Potential improvements include modifying certain program components, decreasing the number of components, and reducing the equipment required.